Repetitive Mild Traumatic Brain Injury in Rats Impairs Cognition, Enhances Prefrontal Cortex Neuronal Activity, and Reduces Pre-synaptic Mitochondrial Function - Feng, Yin; Li, Keguo; Roth, Elizabeth; Chao, Dongman; Mecca, Christina M.; Hogan, Quinn H.; Pawela, Christopher; Kwok, Wai-Meng; Camara, Amadou K. S.; Pan, Bin (Frontiers in Cellular Neuroscience, 2021)
A major hurdle preventing effective interventions for patients with mild traumatic brain injury (mTBI) is the lack of known mechanisms for the long-term cognitive impairment that follows mTBI. The closed head impact model of repeated engineered rotational acceleration (rCHIMERA), a nonsurgical animal model of TBI, mimics key features of mTBI in humans. Using the rCHIMERA during minimized sedation in rats, this study was designed to characterize mTBI-induced behavioral disruption, underlying electrophysiological changes in the medial prefrontal cortex (mPFC), and associated mitochondrial dysfunction. Rats received 6 closed-head impacts over 2 days at 2 Joules of energy. Behavioral testing included automated analysis of behavior in open field and home-cage environments, rotarod test for motor skills, novel object recognition, and fear conditioning. Following mTBI, rats spent less time grooming and less time in the center of the open field arena. Rats in their home cage had reduced inactivity time 1 week after mTBI and increased exploration time 1 month after injury. mTBI impaired associative fear learning and memory in fear conditioning tests, and reduced short-term memory in novel object recognition test 4 weeks after mTBI. Single-unit in vivo recordings showed increased neuronal activity in the mPFC after mTBI, partially attributable to neuronal disinhibition from reduced inhibitory synaptic transmission, possibly secondary to impaired mitochondrial function. These findings help validate this rat mTBI model as replicating clinical features, and point to impaired mitochondrial functions after injury as causing imbalanced synaptic transmission and consequent impaired long-term cognitive dysfunction.